Beyond Symptoms: A Narrative Counseling Interpretation of First-Year Student Anxiety in Indonesian Higher Education - Abdullah, Azizah; Pohan, Rizky Andana; Putri, Ramtia Darma; Triyono, Triyono; Marimbun, Marimbun; Febriani, Rahmi Dwi (Buletin Konseling Inovatif, 2026)
The transition to higher education is a critical period in which first-year students face new academic demands, financial pressures, social adjustment challenges, and uncertainty about the future. However, limited research has examined how freshmen make sense of and narrate their anxiety, particularly in the Indonesian context. This study aimed to explore the main domains of anxiety among first-semester students in Indonesian public universities and to interpret these experiences through a narrative counseling lens. The study employed a qualitative online survey design with an interpretivist orientation. Data were collected from 199 first-semester students through open-ended questions addressing anxiety-provoking situations, sources of anxiety, and the meanings students attached to their early university experiences. The data were analyzed using reflexive thematic analysis and subsequently interpreted through a narrative counseling perspective. The findings identified four main themes: academic anxiety (41.8%), financial anxiety (23.1%), social anxiety (9.5%), and career anxiety (4.5%), while 21.1% of participants reported no anxiety. Academic anxiety was the most dominant theme and was primarily associated with adjustment to new learning demands and fear of poor performance. Overall, freshmen anxiety emerged not only as emotional distress but also as a narrative of inadequacy, burden, misfit, and uncertainty. This study highlights the need to understand freshmen anxiety as both a psychological and meaning-making process and underscores the relevance of narrative-informed support in higher education settings.